2021
DOI: 10.3389/fvets.2021.760717
|View full text |Cite
|
Sign up to set email alerts
|

Probing Differences in Gene Essentiality Between the Human and Animal Adapted Lineages of the Mycobacterium tuberculosis Complex Using TnSeq

Abstract: Members of the Mycobacterium tuberculosis complex (MTBC) show distinct host adaptations, preferences and phenotypes despite being >99% identical at the nucleic acid level. Previous studies have explored gene expression changes between the members, however few studies have probed differences in gene essentiality. To better understand the functional impacts of the nucleic acid differences between Mycobacterium bovis and Mycobacterium tuberculosis, we used the Mycomar T7 phagemid delivery system to generat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Generation and sequencing of the input library. We generated a transposon library in M. bovis AF2122/97 using the phagemid system as previously described (18,19). Sequencing of the input library showed that transposon insertions were evenly distributed around the genome, and 27,419 of the permissible 66,931 thymine-adenine dinucleotide (TA) sites contained an insertion representing an insertion density of ;41% (see input library Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation and sequencing of the input library. We generated a transposon library in M. bovis AF2122/97 using the phagemid system as previously described (18,19). Sequencing of the input library showed that transposon insertions were evenly distributed around the genome, and 27,419 of the permissible 66,931 thymine-adenine dinucleotide (TA) sites contained an insertion representing an insertion density of ;41% (see input library Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA extraction. Genomic DNA from the input and recovered libraries was isolated by an extended bead beating procedure with detergent-based lysis, phenol-chloroform DNA extraction, and precipitation as previously described (19). DNA quality was assessed by nanospectrometry (DeNovix) and gel electrophoresis and quantified by Qubit analysis using the broad-range assay kit (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this list includes two genes ( aspC and glpD2 ) that are essential in vitro in M. tuberculosis but not in M. bovis (10, 11, 18, 66). Information regarding aspC and glpD2 from Tn-seq approaches is likely to be lacking in M. tuberculosis because Tn mutants will not be represented in the input pool.…”
Section: Resultsmentioning
confidence: 99%
“…We generated a transposon library in M. bovis AF2122/97 using the MycomarT7 phagemid system as previously described (18, 19). Sequencing of the input library showed that transposon insertions were evenly distributed around the genome and 27,751 of the possible 73,536 thymine–adenine dinucleotide (TA) sites contained an insertion representing a saturation density of ∼38% (Supplementary Figure S1 and Supplementary Table S1 -input library).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation